Kawasan Konservasi Maritim dan SDG 14: Prospek Teluk Benoa Bali - Slamet Subekti (Endogami: Jurnal Ilmiah Kajian Antropologi, 2020)
This paper discusses what are the benefits of Marine Protected Area (MPA) in relation to SDG (Sustainable Development Goal) number 14 on marine ecosystems. Furthermore, it is discussed how the prospect of the Benoa Bay coast as an MPA. Sustainable development requires a balance between social inclusion, ecological conservation and economic benefits; but in practice MPA among stakeholders places more importance on one pillar than the other. Then it is reviewed how about the status of Benoa Bay as MPA based on the Minister of Marine Affairs and Fisheries decree number 46/KEPMEN-KP/2019 which has divided into core zones and limited use zones. In this case, the core zone is used for Hinduism ritual activities of local communities, while the one is used for small-scale fisheries and marine tourism activities. Thus, Benoa Bay serves to preserve local wisdom and customs, as well as the locus for religious activities of the Balinese people. Finally,  Benoa Bay as an MPA is part of the success of the indigenous peoples' movement and academic studies to encourage the state's commitment to achieve national and global targets to seek 10 percent of Indonesia's territorial waters as MPA. The prospect of Benoa Bay as an MPA in the future is expected to be in line with the goals of sustainable development with the impact of creating social inclusion, improving the welfare of local communities and ensuring the sustainability of marine ecosystems in the coastal areas of Bali.